Endoscopic retrograde cholangiopancreatography in infantile cholestasis. Issue 1 (January 1991) - Wilkinson, M L; Mieli-Vergani, G; Ball, C; Portmann, B; Mowat, A P
Abstract : The difficulty of distinguishing surgically correctable causes of conjugated hyperbilirubinaemia in infants from other causes means that some infants may undergo laparotomy and intraoperative cholangiography unnecessarily, and others may be referred for surgery too late. In an attempt to improve the diagnostic accuracy in infants with conjugated hyperbilirubinaemia when standard methods produced equivocal results, we have been using prototype paediatric duodenoscopes (PJF 7.5 and XPJF 8.0; Olympus) to perform endoscopic retrograde cholangiopancreatography (ERCP). From 159 infants with conjugated hyperbilirubinaemia, 11 were referred for ERCP, which was performed in nine. In four in whom bile ducts were definitely visualised laparotomy was avoided. Operative cholangiography confirmed patent bile ducts in one in whom visualisation had been uncertain. Three of four in whom bile ducts were not seen had extrahepatic biliary atresia. Visible bile drainage in the fourth excluded atresia. No major complications ensued but there was radiological evidence of gall bladder perforation in one (common hepatic duct block) and overinflation with air was a problem until finer cannulae (Wilson-Cook) were introduced. In appropriately selected patients with conjugated hyperbilirubinaemia, ERCP with paediatric duodenoscopes in experienced hands may provide useful diagnostic information.